PENGEMBANGAN KAWASAN WISATA KECAMATAN RUPAT UTARA KABUPATEN BENGKALIS - Muhammad Rheza; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The tourist attractions Rupat North is the potential of the region that must be developed to improve the welfare of society's economy. The development of tourist Rupat North has not changed a very significant. The purpose of research to find out how the development of and factor inhibiting the development of the tourist area concept is used Development of the tour by (Wardiyanto, 2011) of tourist attractions, accommodation facilities, facilities, human resource, service facilities and unsure institutional. The research method used is the research a qualitative with case studies, the source using a technique Purposive sampling. The data collection through observation, interviews and documentation. This research result the development of the tourist area Rupat North can come to fruition by local governments the Bengkalis District. Factor inhibitors include regional budgets are limited and limited land owned. I think the government the Bengkalis District more concerns there and make improvements from accommodation facilities, facilities, transportation, facilities layananan, so that the problem of the tourist area can only be realized with good.Keywords : Development, The Tourist Area, Tourist Attractions